A method to obtain monosporic cultures of arbuscular mycorrhizal fungi - Fracchia, Sebastian (2001)
We describe here a simple technique for obtaining monosporic cultures of AM fungi. Gigaspora rosea, Gi. sp., Glomus mosseae and G. sp. were used. One surface-sterilized spore was transferred to a 5-cm diameter Petri dish with 10 ml of 10 mM MES buffer, plus 0.04 g of Gel-Gro. The contents of a vermiculite-perlite (1/1, v/v) dish with 2-week-old clover seedlings were transferred onto the Gel-Gro medium with the germinated spore. All plants inoculated with single germinated spores developed mycorrhizas. With this system, non-destructive observation of development of hyphae, formation of fan-like structures, hyphal contact and penetration of AM fungi into the plant root was possible.